2010
DOI: 10.4236/ijg.2010.12012
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability of Soil Moisture

Abstract: The characterization of temporal and spatial variability of soil moisture is highly relevant for understanding the many hydrological processes, to model the processes better and to apply them to conservation planning. Considerable variability in space and time coupled with inadequate and uneven distribution of irrigation water results in uneven yield in an area Spatial and temporal variability highly affect the heterogeneity of soil water, solute transport and leaching of chemicals to ground water. Spatial var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…In the case of semi-arid and arid regions, this parameter is particularly important for water resources and irrigation management decisions, understanding land surface processes, and estimating runoff and soil erosion potential [1]. Spatio-temporal soil moisture information is increasingly used as input or a means of validation for multi-hydrological water balance models [2]. The spatial distribution of water in the soil varies both vertically and laterally, as a consequence of variations in precipitation and evapotranspiration, and the influences of topography, soil texture, and vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of semi-arid and arid regions, this parameter is particularly important for water resources and irrigation management decisions, understanding land surface processes, and estimating runoff and soil erosion potential [1]. Spatio-temporal soil moisture information is increasingly used as input or a means of validation for multi-hydrological water balance models [2]. The spatial distribution of water in the soil varies both vertically and laterally, as a consequence of variations in precipitation and evapotranspiration, and the influences of topography, soil texture, and vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…Downer and Ogden (2003) estimated soil moisture using gridded surface subsurface hydrologic analysis (GSSHA) hydrologic model with a root mean square error of 0.1. Pandey and Pandey (2010) mapped soil moisture in Udaipur, India, applying ordinary kriging. The study concluded that the krigged values were consistent and true representative of soil moisture values.…”
Section: Introductionmentioning
confidence: 99%
“…Spatially and temporally varying soil moisture has been increasingly used as an input parameter to hydrological and meteorological models as soil moisture plays a crucial role in the surface runoff of water originating from heavy rainfalls [1]. The spatial distribution of soil moisture varies as a function of the spatial distribution of evapotranspiration and precipitation, ultimately influ-enced by topography, soil texture, and land use type [5][6][7][8]. Alternatives to collecting sufficient knowledge on its spatial distribution include high resolution in situ measurement and monitoring [17,18] or satellite remote sensing applications [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…One way to estimate the magnitude of runoff and peak discharge values is the use of rainfall-runoff numeric models [5,6]. However, such models require accurate spatial parameterization of antecedent catchment states [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation